GE_GERICHTE P/18629/2013 vom 28. April 2016 - GE Cour de justice (2016)
SÉJOUR ILLÉGAL; DROIT DES ÉTRANGERS; ACQUITTEMENT; INDEMNITÉ POUR DÉTENTION; AVOCAT; HONORAIRES | LEtr.115.1.b; CPP.428; CPP.429